Large-field-of-view imaging by Multi-Pupil Adaptive Optics - Park, Jung-Hoon (Nat Methods, 2017)
For in vivo deep imaging at high spatiotemporal resolutions, we developed Multi-Pupil Adaptive Optics (MPAO) which enables simultaneous wavefront correction over a large imaging field-of-view. The current implementation improves correction area by nine times over that of conventional methods. MPAO’s capability of spatially independent wavefront control further enables 3D nonplanar imaging. We applied MPAO to in vivo structural and functional imaging of biological dynamics in mammalian brain.